2018
DOI: 10.4103/ija.ija_156_18
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect low skill fibre-optic intubation: A randomised crossover manikin study of six supraglottic airway devices

Abstract: Background and Aims:Fibre-optic intubation (FOI) through supraglottic airway devices (SADs) is useful in the management of the difficult airway. We compared two methods of FOI through seven SADs in a randomised crossover manikin study to assess each device's performance and discuss implications on SAD selection.Methods:Thirty anaesthetsiologists, 15 seniors and 15 juniors, each performed low skill FOI (LSFOI) with seven SADs using both 'direct' and 'indirect' methods. The order of method and device used were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…SAGFBI can be performed using either the direct or indirect method [57]. In our case series, we only used the direct method (see above).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAGFBI can be performed using either the direct or indirect method [57]. In our case series, we only used the direct method (see above).…”
Section: Discussionmentioning
confidence: 99%
“…The bronchoscope and SAD are then removed whilst keeping the AIC within the trachea, and only then is a tracheal tube railroaded over the AIC. This method is more complex, takes longer to perform and, when transitioning between the various steps involved, airway control and the ability to conventionally ventilate the patient are lost [57].…”
Section: Discussionmentioning
confidence: 99%
“…However, manikin studies showed no difference in SAGFBI times and success rates regardless of operator experience. [ 15 ] This supports junior anesthetists performing SAGFBI following failed intubation.…”
Section: Discussionmentioning
confidence: 59%
“…A manikin study comparing six SADs has reported higher success rate of fibreoptic aided tracheal intubation through Ambu® AuraGain™ than other devices. [ 17 ] This device is also made up of phthalate-free material. The phthalates are known to alter the endocrine system, interfere with steroid genesis and impede with luteal function in females.…”
Section: Discussionmentioning
confidence: 99%